Measles outbreak risk assessment for transplant candidates and recipients. Issue 1 (29th September 2020) - Kreiger‐Benson, Elana; Gelb, Bruce; Neumann, Henry J.; Hochman, Sarah; Lighter, Jennifer; Mehta, Sapna A.
Abstract : Solid organ transplant (SOT) candidates and recipients are at risk of significant morbidity and mortality from infection, including those circulating in the community from unexpected outbreaks. In late 2018‐summer of 2019, a measles outbreak occurred in the New York City area, with a total of 649 cases reported. We developed a systematic 3‐part approach to address measles risk in our adult SOT program through: (a) identification of nonimmune adults living in outbreak ZIP codes, (b) education focused on risk reduction for patients from outbreak ZIP codes, and (c) risk reduction for nonimmune patients. All waitlisted or previously transplanted patients residing in outbreak areas received a measles patient education handout. The electronic medical record of patients born in or after 1957 was reviewed for serologic evidence of measles immunity. Measles immunity testing was performed in patients without documentation of immunity. Patients who tested nonimmune were offered MMR vaccination or intravenous immunoglobulin depending on their transplant phase and risk profile. Thus, we demonstrate successful implementation of a systematic risk assessment during a large measles outbreak to identify and protect at‐risk SOT patients. As vaccine hesitancy persists, our strategies may be increasingly relevant to transplant centers and those caring for immunocompromised patients. Abstract : Systematic risk assessment during a large measles outbreak identifies and protects at‐risk solid organ transplant patients, illustrating an applicable approach for future outbreaks.